Analysis of health and wellness programs and their relationship to injuries in football and futsal players: a systematic review - Cristiana Mercê; Bárbara Tavares; Rafael Oliveira (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2025)
Introduction: Football and futsal are associated with a high risk of injuries and consequently, the development of mental health problems. Health and wellness programs aimed at reducing the incidence of injuries, but these areas remain insufficiently explored in the literature, therefore, their effectiveness is still uncertain.